Juridical Analysis of Corruption Crimes in the Management of DPPA SKPD in the DPRD - Jagar Desprianto Sinaga; Lidya Ramadhani Hasibuan (Journal Evidence Of Law, 2026)
This research will discuss the legal analysis of the application of criminal law on corruption in the management of DPPA SKPD in the DPRD and align the application of laws related to research and thesis, then discuss the obstacles that exist in law enforcement in decision-making related to corruption cases in the management of DPPA SKPD in the DPRD Labuhan Batu. The formulation of the problem of this research is: How do Criminal Acts Obstruct the Corruption Judicial Process According to Law Number 31 of 1999 Junto Law Number 20 of 2001? And how is the Legal Analysis of Criminal Acts of Corruption in the Management of DPPA SKPD in the DPRD? This research uses descriptive research analysis. The type of research used in this research is normative legal research obtained from secondary data. The data collection method used is data collection with document studies which is a method of collecting data through information obtained from documents related to the title of the research raised. Basically, the funds obtained come from the state treasury, where the funds must be used in accordance with the regulations stipulated when withdrawing funds from state finances.